2008
DOI: 10.1103/physrevb.77.132406
|View full text |Cite
|
Sign up to set email alerts
|

Impact of in-plane currents on magnetoresistance properties of an exchange-biased spin valve with an insulating antiferromagnetic layer

Abstract: The impact of in-plane alternating currents on the exchange bias, resistance, and magnetoresistance of a Co 85 Fe 15 / Ni 0.85 Co 0.15 O / Co 85 Fe 15 / Cu/ Co 85 Fe 15 spin valve is studied. With increasing current, the resistance is increased while the maximum magnetoresistance ratio decreases. Noticeably, the reversal field of the pinned layer is systematically suppressed in both field sweeping directions. Since Ni 0.85 Co 0.15 O is a good insulator, it is expected that the ac flows only in the Co 85 Fe 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…8 Several experiments have observed that electrical current influences the exchange bias. 9,10,11,12,13,14 This provides indirect evidence that a spin-polarized current can influence antiferromagnets. However, the exact origin of the observed effect is not clear since exchange bias is a complex and not completely understood phenomenon.…”
Section: Nonrelativistic Spintronics Effectsmentioning
confidence: 93%
“…8 Several experiments have observed that electrical current influences the exchange bias. 9,10,11,12,13,14 This provides indirect evidence that a spin-polarized current can influence antiferromagnets. However, the exact origin of the observed effect is not clear since exchange bias is a complex and not completely understood phenomenon.…”
Section: Nonrelativistic Spintronics Effectsmentioning
confidence: 93%
“…The results of Dai et al [36] indicate that Joule heating plays a major role in the CIP-MR measurements of their EBSV. They used a standard four-probe method to measure the CIP-MR of sputtered AFM/F/N/F spin valves with AFM = 40 nm of NiCoO, pinned F = 3 nm of CoFe, N = 3.8 nm of Cu and free F = 4.5 nm of CoFe.…”
Section: Initial Experiments: Antiferromagnetic Spin-transfer Torque-current-in-plane Experimentsmentioning
confidence: 97%
“…Furthermore, nonuniform current flows inherent to the point-contact technique (Wei et al, 2007) give only a qualitative picture. In addition experiments are sometimes perturbed by unstable antiferromagnetic configurations (Urazhdin and Anthony, 2007) or reconfiguration originating from Joule heating and not spin-transfer torque (Tang et al, 2007(Tang et al, , 2010Dai et al, 2008). New experimental geometries and stacks symmetries need to be proposed to obtain quantitative data.…”
Section: Seeking Spin-transfer Torque Experimentallymentioning
confidence: 99%